TANTANGAN DAN PELUANG: DINAMIKA KEBEBASAN BERAGAMA DI ERA DIGITAL - Qomariyah, Nurul; Munir, Munir; Karoma, Karoma (Peneliti.net, 2025)
This article aims to analyze the dynamics of religious freedom in the digital era with a focus on the challenges and opportunities arising from the development of information and communication technology. The research uses a qualitative approach with analytical descriptive method. Data collection was conducted through literature and documentation studies, with primary data in the form of official documents on religious freedom regulations, research reports, and statistics on intolerance cases in digital media. Data analysis used the Miles and Huberman interactive model with source triangulation to ensure data validity. The results show that the digital era presents challenges in the form of the spread of inaccurate information and hate speech that can threaten tolerance between religious communities. However, on the other hand, digital technology also opens up opportunities for the creation of broader interfaith dialogue through online forums and webinars. The research found that stricter regulations on social media content and education for the public on religious tolerance are needed.